Interaction of instructor and students in classroom of physical education - E. M. Batenko (Омский научный вестник: Серия "Общество. История. Современность")
Physical education is a part of the whole pedagogical process, in particular, its educational component. The goal of physical education is to form a physical culture of personality. In the article questions and ways of the decision of interaction of the teacher and the student on employment of physical training are considered